Strategies to start up sustainable academe-industry collaboration in Metro-Clark - Galguerra, Edzel Gojo Cruz (University of the Philippines Diliman, 2014)
Clarkfield Freeport Zone is one of the emerging investment destinations in the country today. The promulgation of Clark in 2012 as center of excellence in Information and Communication Technology made inter-organizational collaboration, particularly between academe and industry, organizational collaboration, particularly between academe and industry, vitally important. The Metro-Clark ICT Council recognized the need and sought to develop an integrative environment where stakeholder organizations can communicate. While the incidences of cooperation and coordination are notable, an effective and sustainable collaboration has not been fostered and formalized. The main research problem hinges on what are the well-grounded strategies that can be employed to start up sustainable academe-industry collaboration in Metro-Clark. Collaboration, particularly between academe and industry, cannot be fully effective unless it is guided by strategy. The study used a descriptive research design with combined qualitative and quantitative approach through interviews and survey. Both quantitative and qualitative data were analyzed to address the research question. Analysis of the local situations (i.e. interest, attitude, network structure, domain, and barriers to collaboration) prior to formulation of the strategies was undertaken as part of the strategic management process. A framework to start up sustainable academe-industry collaboration in Metro-Clark is presented.